PENGARUH SUMBER DAYA TERHADAP IMPLEMENTASI PERATURAN DAERAH KABUPATEN KAYONG UTARA NOMOR 23 TAHUN 2010 TENTANG PAJAK RESTORAN DI DINAS PENDAPATAN, PENGELOLAAN KEUANGAN DAN ASET DAERAH (DP2KAD) KABUPATEN KAYONG UTARA - Beni Arya Dwinanto E.42009069 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2021)
This research target is to know and analyse the Resouerce influence to Implementation of Law of Kayong Utara Regency of Number 23 year 2010 about Tax Restoration On Earnings, Monetary Management and Asset of Area of Kayong Utara Regency Agency Services. Through statistical test of simple linear regression by using existing population amount by 33 people. Result of research indicates that there is correlation coefficient (R) equal to 0,757 and equation of regresi Y = 2,729 + 0,554 X. Pursuant to statistical analysis, indicators of this research have the characters of valid and reliable. Hypothesis result indicates that the test F obtained from Fcount equal to (41,493) Ftable (4,17) with the probability values = 0,000 smaller than probability values 0,05 which is means Ha accepted and Ho refused. Matter of this Resources have an significantly effect to effectiveness of Implementation of Law of Kayong Utara Regency of Number 23 year 2010 about Tax Restoration. Key Words: Resources and Implementation of Law of Kayong Utara Regency of Number 23 year 2010 about Tax Restoration.